The phenomenology of experiencing non-normative crises of the parent family - Novak, Natalia G. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
A theoretical review of the problem of personal experience of crisis events is presented. The concept of family crisis is considered as a destabilisation of the family system, leading to its dysfunctionality. Normative (transitional moments between the stages of the family life cycle) and non-normative (significant turns of the family life path) family crises are compared. The article describes constructive and destructive options for responding to a crisis in the family system, as well as the conditions that influence this choice. The author analyses the crisis events that are most common during the period of living in the parent family (divorce, serious illness or death of a family member), reveals the features of the process of experiencing them by children (psychoemotional reactions and behaviours). It is emphasised that as a result of experiencing a family crisis, there is an accumulation of experience, which results in changes in each family member (values, meanings, beliefs, ways of responding to a crisis situation) and the family system as a whole. It is indicated that when providing psychological assistance to family members, it is important to study the content of the experience, as well as to study the consequences of the experience in order to identify factors that promote or hinder their personal growth.
Keywords: experience; crisis; crisis event; system approach; family system; experience of experience